The Impact of Celebrity News on Entertainment Industry Stock Prices - Ariani, Alexandra Widuri; Husodo, Zaäfri Ananto (UI Scholars Hub, 2024)
South Korea's entertainment industry has garnered global popularity. However, the competition between entertainment companies is fierce, necessitating strategies to ensure their survival, such as imposing restrictions on their artists to maintain their public image and trust. This study examined the impacts of celebrity news and activities on the stock returns of six major entertainment companies listed on the Korea Exchange (KRX) from 2018-2021. Employing the Fama-French 3 Factors Model regression, the study investigated the presence of abnormal returns. The findings indicate that comebacks and debuts elicit positive reactions and generate significant abnormal returns. Award acceptances and military service also elicit positive reactions but do not generate significant abnormal returns. Dating news, internal scandals, and national scandals elicit negative reactions. However, only national scandals generate significant abnormal returns. These findings imply that entertainment companies and investors should actively manage and monitor celebrity news to make informed decisions.